Effects of positive education intervention on growth mindset and resilience among boarding middle school adolescents in China: a randomized controlled trial - Jianping, Gao; Roslan, Samsilah; Soh, Kim Geok; Zaremohzzabieh, Zeinab (Frontiers in Psychology, 2024)
Introduction The impact of a growth mindset and resilience on boarding middle school adolescents has received increasing attention from scholars. Nevertheless, research on how to intervene in the growth mindset, and resilience of boarding school adolescents needs further verification. The purpose of this study is to explore whether positive education intervention based on the PERMA (positive emotions, engagement, relationships, meaning, and achievement) model will help Chinese boarding middle school adolescents improve their growth mindset and resilience. Methods This study is a randomized controlled trial with both a control group and an experimental group, including pre-tests and post-tests. The study subjects were 167 adolescents, including 84 (n1 = 84) adolescents in the experimental group and 83 (n2 = 83) adolescents in the control group. Results The results showed that adolescents under the intervention condition reported significantly improved growth mindset and resilience. Discussion Compared with the control group, resilience significantly increased. These findings indicate that positive educational intervention is a promising approach to improve boarding adolescents ‘growth mindset and resilience.